Immigration Enforcement and the Institutionalization of Elderly Americans - Abdulmohsen Almuhaisen; Catalina Amuedo-Dorantes; Delia Furtado (Institute of Labor Economics (IZA), 2023)
This paper examines the relationship between immigration enforcement and institutionalization rates of the elderly. Exploiting the staggered implementation of the Secure Communities (SC) immigration enforcement program across U.S. counties from 2008 through 2014, we show that SC led to a 0.26 percentage points (6.8 percent) increase in the likelihood that Americans aged 65 and above live in an institution. Supportive of supply shocks in the household services market as a central mechanism, we find that the elderly who are most likely to purchase domestic worker services are also the most likely to move into nursing homes following the implementation of SC. Additionally, we find suggestive evidence of significant reductions in the work hours of housekeepers, personal care aids, and home health workers hinting at the critical role of negative supply shocks in occupations that facilitate aging in community.
Keywords: J14; J61; J68; 330; secure communities; elder care; immigration enforcement; aging; nursing homes